INCAPACITY OF A PARTY IN ARBITRATION: GENERAL APPROACHES AND LIMITATIONS OF DEFENSE - Elamsius Sinaga , Gregorius Made (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2022)
According to Article V(1)(a) of the New York Convention, the recognition and enforcement of an arbitral award may be refused, if the parties involved, under the ‘law applicable to them’, were under some incapacity when entering into an arbitration agreement. However, this specific provision is considered one of the most uncertain aspects of the Convention as it has caused challenges from its structure and wording which do not explicitly set the concept of capacity nor the governing law and other essential circumstances related to this defense. Furthermore, the absence of standards in this defense makes a significantly different interpretation by courts causing legal uncertainties to all the parties involved in the proceeding. In this paper, the author examines general approaches for determining the governing law on a capacity of a party in arbitration and analyzes limitations on the defense of incapacity in arbitration-friendly jurisdictions. The approach employed is normative juridical, relying on qualitative analysis of secondary data. This paper covered the choice of law method and the substantive law method in determining the law governing capacity of a party in entering an arbitration agreement. In the end, the paper explored various laws that limit the state from invoking incapacity initially established in the Lizardi case in France.